Improved Thermoelectric Properties and Environmental Stability of Conducting PEDOT:PSS Films Post-treated With Imidazolium Ionic Liquids - Yemata, Temesgen Atnafu; Zheng, Yun; Kyaw, Aung Ko Ko; Wang, Xizu; Song, Jing; Chin, Wee Shong; Xu, Jianwei (Frontiers in Chemistry, 2020)
PEDOT:PSS is one of the most popular conducting polymers and widely used as polymer thermoelectric materials. Its thermoelectric performance could be improved by a variety of post-treatment processes. This paper reported two series of post-treatment methods to enhance the thermoelectric performance. The 1st series method included pre-treatment of PEDOT:PSS film with formamide, followed by imidazolium-based ionic liquids. The 2nd series method included pre-treatment of PEDOT:PSS film with formamide, followed by sodium formaldehyde sulfoxylate, and finally imidazolium-based ionic liquids. Two series of post-treatment methods significantly improved the power factor of PEDOT:PSS when compared to that of PEDOT:PSS treated with formamide only. For example, using the 1st series post-treatment method with 40 vol.% ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl) amide, the Seebeck coefficient of the PEDOT:PSS film increased from 14.9 to 28.5 µV/K although the electrical conductivity reduced from 2,873 to 1,701 S/cm, resulting in a substantial improvement in the overall power factor from 63.6 to 137.8 µW/K2m. In contrast, 2nd series post-treatment method led to the reduction in electrical conductivity from 2,873 to 641 S/cm but a big improvement in the Seebeck coefficient from 14.9 to 61.1 µV/K and thus the overall power factor reached up to ~239.2 µW/K2m. The environmental stability of ionic liquid-treated PEDOT:PSS films were examined. It was found that the ionic liquid treated PEDOT:PSS retained more than 70% Seebeck coefficient and electrical conductivity at 75% RH humidity and 70 oC for 480 hours. The improved long-term TE stability is attributed to the strong ionic interaction between sulfonate anions and bulky imidazolium cations that effectively block the penetration of water and lessen the tendency to take up water from the air.